AN ORDER-PARAMETER APPROACH TO COEXISTENCE IN ATOMIC CLUSTERS - Doye, J; Wales, D (1995)
We employ order parameters to investigate the dynamic equilibrium between the two lowest energy geometric isomers of LJ8, between permutational isomers of the global minimum of LJ14, and between solidlike, surface-melted, and liquidlike forms of LJ55. For LJ55 approximate analytical calculations which use only information derived from the potential energy surface can accurately model the equilibrium between the different forms. This approach provides a further illustration of how different regions of the potential energy surface influence the thermodynamics. Low-energy transition states are characterized to improve our understanding of the dynamics in the "surface-melted" phases. Finally, using a two state model, we consider the size dependence of the conditions necessary to produce an S-bend (Van der Waal's loop) in the microcanonical calorie curve. © 1995 American Institute of Physics.